뇌성마비아동의 지각-운동 통합능력의 평가 및 분석 - 심규학 (연세대학교 보건대학원, 1991)
[한글] 이 연구의 목적은 뇌성마비아동의 지각능력, 운동능력, 시각-운동 통합능력을 연령별, 성별, 장애유형별로 구분하여 그 발달수준을 비교하는 한편 지각, 운동, 시각-운동 통합검사와 연령간의 상관관계를 분석해 보고자 하였다. 지각-운동 발달검사(Perceptual-Motor Development Test: PMDT)와 시각-운동 통합 발달 검사(Development Test of Visual-Moter Integration: VMI)도구를 사용하여 5-11세의 뇌성마비아동 80명을 대상으로 검사 실시 요강에 따라 검사 및 채점을 한 후 지각검사, 운 동검사, VMI검사별로 얻은 점수에 따라 발달연령(developmental age)을 구하고, 그 발달연령과 생활연령(chronological age)의 비율에 의하여 발달지수를 산출하였다. 연구 변수(연령, 성, 장애유형)별 지각-운동 통합능력의 발달수준을 평가하고, 연령과 각 하위검사(지각, 운동, VMI검사)간의 상관관계를 분석한 결과는 다음과 같다. 1. 연구 대상 아동들의 지각-운동 통합능력은 생활연령에 비하여 발달 연령이 평균 38.48개월(약 3년 2개월) 정도 늦었다. 2. 뇌성마비아동의 생활연령이 증가함에 따라 지각-운동 통합능력도 발달하였지만, 그 속도는 매우 느렸다. 3. 성별 및 장애유형에 따른 뇌성마비아동의 지각-운동 통합능력간에는 통계적인 유의차가 없었다. 4. 연령이 증가함에 따라 경직성아동이 불수의운동형아동보다 지각-운동통합능력의 발달정도가 더 높은 특성을 보였다. 5. 연구 대상 아동들의 운동발달이 지각발달보다 더 늦었으며, 특히 운동능력중에서 점 찍기 능력이 선 긋기 능력보다 낮았다. 6. 지각, 운동, VMI검사와 연령간의 상관관계는 운동검사와 VMI검사간에서 가장 높게 나타났다(r = 0.6124). 이 연구의 결과에 의하면 뇌성마비아동의 지각-운동 통합능력은 발달속도는 느리지만, 연령의 증가에 따라 그 능력도 발달함을 알 수 있다. 지각-운동능력이 학습준비기능으로서의 중요한 요소임을 깨닫고, 뇌성마비아동의 지각-운동능력의 발달수준과 특성을 정확히 파악하여 각각의 아동에게 알맞은 훈련과 지도로 그 능력을 향상시켜 주는 것은 매우 중요한 과제라고 사료된다. 앞으로는 시지각과제 이외에도 기타의 감각기능(청각, 촉각, 후각, 미각등)을 통한 제반 지각-운동 통합능력의 발달을 위한 효과적인 프로그램의 개발과 지도방법에 관한 전향적인 연구가 시도되어야 할 것이다. [영문] The objectives of this study were (1) to clarify perceptual ability, motor ability, and visual-motor integration ability of cerebral palsied children by age, sex, and disorder type, (2) to compare developmental level of the children, and (3) to analyse the correlation of age with perception, motor, and visual-motor integration. In order to collect data, Perceptual-motor Development Test (PMDT) and Development Test of Visual-motor Integration(VMI) were used. These tests were performed on eighty cerebral palsied children aged from five to eleven. Developmental age was calculated from perception test, motor test, and VMI test. Then, developmental index was figured out via the ratio of developmental age and chronological age. After the evaluation of developmental level of the perceptual-motor integration ability in terms of each research variable(i.e., age, sex, disorder type), and the correlation analysis between age and each tested factor(i.e., test scores of perception, motor, VMI),following results were derived: 1. On the average, developmental age of the children's perceptual-motor integration ability was lower than chronological age by 38.48 months(3 years and 2 months). 2. Perceptual-motor integration ability of cerebral palsied children increased as their chronological age increase. However, the rate of development was very slow. 3. In terms of age difference or disorder type, there was no statistically significant difference in the perceptual-motor integration ability of cerebral palsied children. 4. As the age increase, developmental level of the perceptual-motor integration ability of children with spasticity was higher than that of children with athetoid type. 5. The rate of development of motor ability was lower than that of the development of perceptual ability. Among motor abilities, point drawing ability was especially higher than line drawing ability. 6. Among the test scores of perception, motor, and VMI by age, the highest correlation coefficient, was derived between motor and VMI scores. 7. According to the results of this studs, the rate of development of perceptual-motor integration ability of cerebral palsied children was slow. However, this ability increased as the chronological age increase. It is important understanding the importance of perceptual-motor ability as an factor of learning preparation function, as well as understanding the developmental level and the characteristics of the perceptual-motor ability of the children in order to provide them with proper training to develop their ability. Future research should focus on the development of effective program and training procedure to increase perceptual-motor integration ability via other sensory function(i.e., hearing, touching, smelling, tasting) in addition in visual perception function.
보건학과/석사